Bridging particle and wave sensitivity in a configurable detector of positive operator-valued measures. - Puentes, G; Lundeen, J; Branderhorst, M; Coldenstrodt-Ronge, H; Smith, B; Walmsley, I (2009)
We report an optical detector with tunable positive operator-valued measures. The device is based on a combination of weak-field homodyne techniques and photon-number-resolving detection. The resulting positive operator-valued measures can be continuously tuned from Fock-state projectors to a variety of phase-dependent quantum-state measurements by adjusting different system parameters such as local oscillator coupling, amplitude, and phase, allowing thus not only detection but also preparation of exotic quantum states. Experimental tomographic reconstructions of classical benchmark states are presented as a demonstration of the detector capabilities.